The effect of 12-month participation in osteogenic and non-osteogenic sports on bone development in adolescent male athletes. The PRO-BONE study. Issue 4 (April 2018) - Vlachopoulos, Dimitris; Barker, Alan R.; Ubago-Guisado, Esther; Ortega, Francisco B.; Krustrup, Peter; Metcalf, Brad; Castro Pinero, Jose; Ruiz, Jonatan R.; Knapp, Karen M.; Williams, Craig A.; Moreno, Luis A.; Gracia-Marco, Luis
Abstract: Objectives: Research investigating the longitudinal effects of the most popular sports on bone development in adolescent males is scarce. The aim is to investigate the effect of 12-month participation in osteogenic and non-osteogenic sports on bone development. Design: A 12-month study was conducted in adolescent males involved in football, swimming and cycling and compared with an active control group. Methods: 116 adolescent males (13.1 ± 0.1 years at baseline): 37 footballers, 37 swimmers, 28 cyclists and 14 active controls were followed for 12 months. Bone mineral content (BMC) was measured by dual-energy X-ray absorptiometry, and bone stiffness was measured by quantitative ultrasound. Bone outcomes at 12 months were adjusted for baseline bone status, age, height, lean mass and moderate to vigorous physical activity. Results: Footballers had higher improvement in adjusted BMC at the total body, total hip, shaft, Ward's triangle, legs and bone stiffness compared to cyclists (6.3–8.0%). Footballers had significantly higher adjusted BMC at total body, shaft and legs compared to swimmers (5.4–5.6%). There was no significant difference between swimmers and cyclists for any bone outcomes. Swimming and cycling participation resulted in non-significant lower bone development at most sites of the skeleton compared to controls (−4.3 to −0.6%). Conclusions: Football participation induces significantly greater improvements in BMC and bone stiffness over 12 months compared to cycling and swimming. Clinical trial registration: ISRCTN17982776.